2012
DOI: 10.1007/s10664-012-9218-8
|View full text |Cite
|
Sign up to set email alerts
|

Software defect prediction using Bayesian networks

Abstract: There are lots of different software metrics discovered and used for defect prediction in the literature. Instead of dealing with so many metrics, it would be practical and easy if we could determine the set of metrics that are most important and focus on them more to predict defectiveness. We use Bayesian networks to determine the probabilistic influential relationships among software metrics and defect proneness. In addition to the metrics used in Promise data repository, we define two more metrics, i.e. NOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
158
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(160 citation statements)
references
References 43 publications
(42 reference statements)
0
158
0
2
Order By: Relevance
“…Moreover, the studies in [11], [12] discussed various ML techniques and provided the ML capabilities in software defect prediction. The studies assisted the developer to use useful software metrics and suitable data mining technique in order to enhance the software quality.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the studies in [11], [12] discussed various ML techniques and provided the ML capabilities in software defect prediction. The studies assisted the developer to use useful software metrics and suitable data mining technique in order to enhance the software quality.…”
Section: Related Workmentioning
confidence: 99%
“…Tomcat has been largely used for empirical software engineering studies [6,10,7,8,9,14,18,20]. For example, Okutan et al [11] built a Bayesian network among metrics and defectiveness, to measure which metrics were more important in terms of their effect on defectiveness and to explore the influential relationships among them. The authors used 9 datasets from the teraPromise data repository 9 , considering Tomcat among other systems, and showed that RFC, LOC, and LOCQ are more effective on defect proneness.…”
Section: Related Workmentioning
confidence: 99%
“…• Neural Networks In their work, Okutan and Yildiz [5] used a Bayesian networks to determine the set of metrics that are most important and focus on them more to predict defectiveness. They used the Bayesian networks to determine the probabilistic influential relationships among software metrics and defect proneness.…”
Section: Literature Reviewmentioning
confidence: 99%